Induction of Abortion by Extra-amniotic Administration of Prostaglandins E2 and F2 α. Issue 5819 (15th July 1972) - Embrey, M. P.; Hillier, Keith; Mahendran, P.
Abstract : The use of prostaglandins E2 and F2 α, administered by extra-amniotic instillation, for the induction of abortion was studied in 94 patients in the first and second trimesters of pregnancy. Abortion was successfully induced in 87% of patients within 36 hours and in 94% within 48 hours. The mean abortion time was 22·4 hours. In 60% of patients abortion was complete. Though the differences were not statistically significant, on average multigravid patients aborted more quickly than primigravidae, while the mean abortion time in PGE2 -treated patients was less than in those receiving PGF2 α. No serious complications occurred. Some side effects were observed. Occasional vomiting was the commonest symptom but the incidence of side effects was lower than with alternative routes of administration. A leucocytosis was often noted but there were no significant instances of infection. The method has proved a safe and effective means of terminating pregnancies in the second trimester.